Semantic Analysis Of Mantra Pawang Hujan In Kota Tebing tinggi-North Sumatra - Zusfahmi Alfaginda (Universitas Muhammadiyah Sumatera Utara, 2021)
This study aimed to analyze the types of meaning and the description of meaningwords/phrase/sentencess used in the Mantra Pawang Hujan. Geoffrey Leech Theory was applied in this study. A descriptive qualitative research was appliedto analyze the data. Source of data was in the form of spoken form of Mantra Pawang Hujan from two local pawang. They were transcribed into the written form which consisted of word/phrase/sentence.Data were collected through observation, depth interview, and documentation. There were 23 word/phrase/sentence as data in Mantra Pawang Hujan 1, and 17 word/phrase/sentence in Mantra Pawang Hujan 2. After analyzing the data, it was found 6 types of meaning appeared in Mantra Pawang Hujan 1, namely; conotative meaning, social meaning, reflective meaning, thematic meaning, collocative meaning and affective meaning. Meanwhile there were 4 types of meaning found in Mantra Pawang Hujan 2, namely; conotative meaning, social meaning, conceptual meaning and affective meaning.The meaning of words/phrase/sentences communicated by the two pawang is not far from the actual meaning. Mostly, the expression used by pawang 2 is the real meaning, because the words/phrase/sentencess are pray, praises or a compliment to the Almighty God and also based on Quran. Keywords : semantics, types of meaning, mantra pawang hujan